2016
DOI: 10.1159/000446656
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Gonadal Axis in Aging Men and Women: Increasing Total Testosterone in Aging Men

Abstract: Background: Aging is associated with variations in hypothalamic-pituitary-gonadal (HPG) axis hormones. However, it is not clear how aging changes these hormones. This study examined the natural alterations in the HPG axis in aging men and women in China. Methods: Data were obtained from our cross-sectional study (SPECT-China) in 16 areas of three provinces in East China between February and June 2014. There were 6,825 subjects selected, including 2,908 men and 3,917 women aged 25-93 years who had no diseases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…It is interesting that we found TT increased with aging in men in our study, which was elaborately discussed in our previous paper [ 34 ]. T is the major androgen in males and 95% of T is secreted by Leydig cells, most of which adhere with the sex hormone-binding globulin (SHBG).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…It is interesting that we found TT increased with aging in men in our study, which was elaborately discussed in our previous paper [ 34 ]. T is the major androgen in males and 95% of T is secreted by Leydig cells, most of which adhere with the sex hormone-binding globulin (SHBG).…”
Section: Discussionsupporting
confidence: 71%
“…Recently, Kelsey et al [ 40 ] analyzed a dataset obtained from 13 studies ( n = 10,097; age range 3–101 years) regardless of ethnicity and found no evidence to support a progressive decline in T in middle-aged and older men. In our population, age-related increases of SHBG and declining clearance by the kidneys could partially explain the pattern of changes in TT with age in Chinese men [ 34 ]. Moreover, we found that the LH levels in Chinese men were positively associated with TT, which suggests that the testicular responsiveness to LH in Chinese men was not decreased to the same degree as in other populations [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of total T measured by the IMMULITE 2000 platform are not reliable when they are at low concentrations, as observed in women. 35 The phases of the menstrual cycle and age of menopause for the women were not available. In addition, the effect of pregnancy on TN formation was considered.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent cross-sectional study of 2,908 men in China, there was no decrease in total testosterone with age, although sex hormone-binding globulin (SHBG) and serum LH both increased with age, suggesting a degree of compensation for testicular insensitivity and the possibility of a decline in free testosterone levels [4]. Similarly, Kelsey et al [5] did not find any evidence of a further reduction in total testosterone beyond the age of 40 years, although there was increased variability in total testosterone at older ages.…”
Section: Introductionmentioning
confidence: 99%